Treinamento e desenvolvimento de liderança situacional: capacitando líderes flexíveis e adaptáveis para o sucesso em ambientes dinâmicos - SILVA, Alexandra Cristina Borges da; SILVA, Fernanda Rodrigues da; MIRANDA, Magda Noronha; RODRIGUES, Rebeca Pires; SOUZA, Vanessa dos Santos (194, 2025)
Liderança Situacional é um método de liderar que se originou da teoria de dois estudiosos, Paul Hersey e Kenneth Blanchard. É def inida como a capacidade de adaptação de um líder diante do contexto do mercado, gerindo equipes de alto desempenho mesmo em situações de crise e com uma atuação madura, empática e analítica, promovendo uma gestão mais ef icaz e f lexível, capaz de desenvolver seguidores e alcançar melhores resultados. Por meio da Liderança Situacional, podese identif icar perf is, mapear competências, oferecer treinamentos personalizados, acompanhar a evolução e fortalecer uma cultura organizacional adaptativa. Com o objetivo de avaliar os critérios utilizados pela empresa X para a participação dentro desses programas que estejam envolvidos na produção. Investigar os impactos desses programas no desempenho prof issional dentro da organização. Pesquisar os desaf ios enf rentados pelas empresas na implementação e manutenção desses programas.

Summary: Situational Leadership is a leadership method that originated from the theory of two scholars, Paul Hersey and Kenneth Blanchard. It is defined as the ability of a leader to adapt to the market context, managing high-performance teams even in crisis situations, with mature, empathetic, and analytical behavior, promoting more effective and flexible management capable of developing followers and achieving better results.Through Situational Leadership, it is possible to identify profiles, map competencies, provide personalized training, monitor progress, and strengthen an adaptive organizational culture.The objective is to evaluate the criteria used by Company X for participation in these programs for those involved in production, investigate the impacts of these programs on professional performance within the organization, and research the challenges faced by companies in implementing and maintaining these programs

Summary: Situational Leadership is a leadership method that originated from the theory of two scholars, Paul Hersey and Kenneth Blanchard. It is defined as the ability of a leader to adapt to the market context, managing high-performance teams even in crisis situations, with mature, empathetic, and analytical behavior, promoting more effective and flexible management capable of developing followers and achieving better results.Through Situational Leadership, it is possible to identify profiles, map competencies, provide personalized training, monitor progress, and strengthen an adaptive organizational culture.The objective is to evaluate the criteria used by Company X for participation in these programs for those involved in production, investigate the impacts of these programs on professional performance within the organization, and research the challenges faced by companies in implementing and maintaining these programs
Training and development of situational leadership: empowering flexible and adaptable leaders for success in dynamic environments.
Keywords: Liderança; Treinamento de pessoal; Gestão e Negócios